2021
DOI: 10.3390/ma14041049
|View full text |Cite
|
Sign up to set email alerts
|

Porous Zirconia/Magnesia Ceramics Support Osteogenic Potential In Vitro

Abstract: Porous zirconia (ZrO2), magnesia (MgO) and zirconia/magnesia (ZrO2/MgO) ceramics were synthesised by sintering and designated as ZrO2(100), ZrO2(75)MgO(25), ZrO2(50)MgO(50), ZrO2(25)MgO(75), MgO(100) based on their composition. The ceramic samples were characterised by means of scanning electron microscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy and atomic absorption spectrometry to explore the incorporation of Mg atoms into the zirconia lattice. The resulting porosity of the samples was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Thus, our results are in agreement with different studies that reported that zirconia nanofibers or ZrO 2 composites may have pro-osteogenic properties, have good mechanical biocompatibility, and improve the metabolism of bone precursor cells. Furthermore, they could also be considered as a self-regulation material that possesses an excellent osteoinductive capacity that could modify the deposition of ECM by bone cells during differentiation or in response to the surface material, because the osteoblast cell functions could be substrate-sensitive, either with respect to stiffness, roughness, or to the size of the composition of the material [16,17,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results are in agreement with different studies that reported that zirconia nanofibers or ZrO 2 composites may have pro-osteogenic properties, have good mechanical biocompatibility, and improve the metabolism of bone precursor cells. Furthermore, they could also be considered as a self-regulation material that possesses an excellent osteoinductive capacity that could modify the deposition of ECM by bone cells during differentiation or in response to the surface material, because the osteoblast cell functions could be substrate-sensitive, either with respect to stiffness, roughness, or to the size of the composition of the material [16,17,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized with excellent aesthetic value because it is a material with a light color and it is also easy to cover with veneering porcelain. ZrO 2 is a biocompatible material [4,[9][10][11]. In addition, clinical studies did not reveal the occurrence of allergies in people with prosthetic restorations on a zirconium oxide substructure, which is the opposite of those restorations on metal, where a large percentage of owners of such restorations have, for example, a bluish discoloration of the gingiva, commonly known as the "gingival margin" [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetics use a tetragonal phase that does not have a glass phase in a structure. It is the most advantageous from the point of view of biomechanics, because it can be stabilized at room temperature by adding oxides of magnesium, calcium, yttrium, or cerium [ 6 , 11 , 12 ]. The material is available in the form of ready-made blocks, which are processed by a milling machine to the prosthetic framework during a sequence of consecutive steps [ 13 ].…”
Section: Introductionmentioning
confidence: 99%